Power allocation of hybrid spectrum sharing based on the spatial location - Yan CAI; Jing ZHANG; Hong-bo ZHU (Tongxin xuebao)
Based on the random spatial location of the secondary user, a spatial hybrid spectrum sharing model which combines overlay with underlay was proposed to improve spectrum utilization. Considering the different location of sec-ondary user, the interference received by primary receiver was analyzed and the work regions of the overlay and underlay were deduced under the primary user average interference constraint. The power allocation model was built under the criterion of maximizing the system average (ergodic) capacity. Furthermore, the optimal power allocation scheme was deduced as well as the maximum achievable capacity of the spatial hybrid spectrum sharing system. Analysis and simula-tion results indicate the hybrid spectrum sharing system has higher capacity than single overlay system.